Pengaruh Citra Merek, Kepercayaan Merek Dan Kualitas Produk Terhadap Kepuasan Konsumen Gen Z Perempuan Produk Emina Di Pangkalpinang - Naibaho, Marco Veril Hamonangan; Sumar, Sumar; Noviyanti, Indah (Universitas Pahlawan Tuanku Tambusai, 2025)
The growing trend of local cosmetic use among female Gen Z consumers has prompted companies to better understand the factors influencing consumer satisfaction. Emina, as one of the leading local brands, faces challenges in maintaining consumer satisfaction despite its high popularity. This study aims to examine the influence of brand image, brand trust, and product quality on the satisfaction of female Gen Z consumers who use Emina products in Pangkalpinang. The research employs a descriptive quantitative approach with a sample size of 100 respondents, selected through purposive sampling. The independent variables in this study are brand image, brand trust, and product quality, while the dependent variable is consumer satisfaction. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The analysis results show that brand image does not have a significant partial effect on consumer satisfaction. Meanwhile, brand trust and product quality have a positive and significant partial effect. Simultaneously, all three independent variables have a significant influence on consumer satisfaction, with an R² value of 77.9%. This research contributes to the development of marketing strategies for local products, especially Emina, by emphasizing the importance of brand trust and product quality to enhance the satisfaction and loyalty of Gen Z consumers. These findings are also valuable for academics as a reference for similar studies.